PEMBANGUNAN MANUSIA, KETIMPANGAN GENDER DAN PERTUMBUHAN EKONOMI DI INDONESIA - Uswatun Hasanah; Ikhsan Ikhsan (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2020)
AbstractThis research discusses the great development of humans, and gender inequality on economicgrowth in Indonesia. The data used in this study are secondary data sourced from the CentralStatistics Agency in the form of data panels and cross sections of 33 provinces in 2010-2018. Themodel used in this study is a multiple linear regression model. Selection of the appropriate model,used the Common Effect Model (CEM), Fixed Effect Model (FEM) and Random Effect Model(REM). From the test results, the Fixed Effect Model (FEM) model was obtained as the appropriatemodel to use. Regression results show that the independent variable is a positive and significant lifeexpectancy on economic growth, while the work participation rate variable has a negative andsignificant effect on economic growth in Indonesia. Because the conclusion of this study is that thegovernment must increase the budget by using the budget, making the budget used for women,because improving women's health and education increases the quality of the female workforce.Keywords: Human development, gender inequality, life expectancy, labor force participation rates,economic growth.